CULTURAL DIFFERENCES IN TRANSLATION: SEMANTIC SHIFTS IN THE ENGLISH-INDONESIAN COMIC OF THE ANDVENTURES OF TINTIN, THE BROKEN EAR - Rahmi, Asyifa (2016)
This research analyzes semantic shifts found in Tintin comic series entitled The Adventures of Tintin, The Broken Ear in English-Indonesian version by using Mujiyanto's (2001) semantic shift categories: generalization, specification, substitution, deviation, and reversal. Descriptive qualitative method was used to give detailed analysis of semantic shifts. Findings show that the use of semantic shift in English-Indonesian version of comic Tintin series may influence the translator in the process of translation. Not only can influence the process of translation, the use of semantic shift also signify many changes of the target text. Such changes happen because the translator is guided by the ethic code of Indonesian translation by Himpunan Penerjemah Indonesia. In addition, cultural differences in English-Indonesian version of comic Tintin series can be seen from how the translator changes the source language into the target language. Furthermore, several suggestions have been mentioned for further study.;--- Penelitian ini meneliti perubahan semantik dalam serial komik Tintin berjudul The Adventures of Tintin, The Broken Ear dalam versi Bahasa Inggris-Indonesia dengan menggunakan kategori perubahan semantik oleh Mujiyanto (2001): generalisasi, spesifikasi, substitusi, deviasi, dan pembalikkan. Metode deskriptif kualitatif digunakkan untuk memberikan analisis mendetail mengenai perubahan semantik. Hasil penelitian menunjukkan bahwa penggunaan perubahan semantik dalam serial komik Tintin versi Bahasa Inggris-Indonesia dapat memengaruhi penerjemah dalam proses penerjemahan. Penggunaan perubahan semantik tidak hanya memengaruhi proses penerjemahan, tetapi juga menunjukkan berbagai perubahan dalam teks yang diterjemahkan (teks target). Perubahan-perubahan seperti itu terjadi karena penerjemah dibimbing oleh kode etika mengenai penerjemahan Bahasa Indonesia yang dibuat oleh Himpunan Penerjemah Indonesia. Selain itu, perbedaan-perbedaan kultural dalam serial komik Tintin versi Bahasa Inggris-Indonesia bisa dilihat dari cara penerjemah mengubah bahasa sumber menjadi bahasa target. Sebagai tambahan, beberapa saran telah disebutkan di dalam penelitian ini untuk penelitian lebih lanjut.